2015
DOI: 10.1016/s2214-109x(14)70368-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of reactive oral cholera vaccination in rural Haiti: a case-control study and bias-indicator analysis

Abstract: Background Between April and June 2012, a reactive cholera vaccination campaign was conducted in Haiti using an oral inactivated bivalent whole-cell vaccine (BivWC). Methods We conducted a case-control study to estimate field effectiveness of the vaccine. Cases had acute watery diarrhea, sought treatment at one of three participating cholera treatment units from October 24, 2012 through March 9, 2014, and had a stool sample positive for cholera by culture. For each case, four controls (individuals who did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 25 publications
3
84
0
Order By: Relevance
“…22 Our colleagues in the Artibonite valley have recently reported an estimated VE of 65% at their site using a casecontrol design. 26 Our study reports that only 18 cases of cholera occurred in the patients who had received at least one dose. Although a small group, this argues for effectiveness of even a single dose of vaccine.…”
Section: Discussionmentioning
confidence: 76%
“…22 Our colleagues in the Artibonite valley have recently reported an estimated VE of 65% at their site using a casecontrol design. 26 Our study reports that only 18 cases of cholera occurred in the patients who had received at least one dose. Although a small group, this argues for effectiveness of even a single dose of vaccine.…”
Section: Discussionmentioning
confidence: 76%
“…In another example, several VE case-control studies for cholera vaccines have used confirmed cholera diarrhea as cases and chose as controls persons who did not seek treatment for diarrhea -a conventional design (65)(66)(67). They then did a parallel "bias-indicator" analysis using those who sought treatment for diarrhea but did not test positive for cholera as cases and conventional controls, showing that the study design did not find measurable VE for a noncholera outcome.…”
Section: Discussionmentioning
confidence: 99%
“…• Showed that the vaccine-preventable burden of influenza mortality has been overestimated due to confounding (6,14,15) • Added confidence to several studies of cholera VE in outbreaks by showing that VE was estimated to be not statistically different from zero for non-cholera diarrhea (65)(66)(67) Substantive insights from test-negative designs…”
Section: Discussionmentioning
confidence: 99%
“…(17) Early OCV effectiveness estimates from this campaign suggested effectiveness of 58 to 63%. (6) Further OCV campaigns using the same vaccine occurred in subsequent years targeting an additional 395,000 people in high cholera-incidence communities.…”
Section: Methodsmentioning
confidence: 99%